2019
DOI: 10.3390/ijms21010017
|View full text |Cite
|
Sign up to set email alerts
|

Association of Complement Factor D and H Polymorphisms with Recurrent Pregnancy Loss

Abstract: Recurrent pregnancy loss (RPL) is defined as two or more consecutive pregnancy losses prior to 20 weeks of gestation, and the incidence of RPL is estimated at 1% of all pregnancies. While the etiologies of RPL are diverse, immune function is considered to be an important cause of RPL. In particular, the complement system is essential for stable development of the placenta and fetus. Moreover, complement factor D (CFD) and complement factor H (CFH) are important regulators of the complement system and are assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 30 publications
0
15
0
1
Order By: Relevance
“…An association with miscarriage was suggested but not significant, and needs to be evaluated in larger cohorts, similar to studies that identified complement variants important in atypical hemolytic uremic syndrome. A different study found that a polymorphism in Factor H was associated with a decrease in risk of recurrent pregnancy loss ( 68 ). Factor H in part controls complement activation on cells by binding to sialic acid.…”
Section: Complement From Implantation Through Placental Developmentmentioning
confidence: 99%
“…An association with miscarriage was suggested but not significant, and needs to be evaluated in larger cohorts, similar to studies that identified complement variants important in atypical hemolytic uremic syndrome. A different study found that a polymorphism in Factor H was associated with a decrease in risk of recurrent pregnancy loss ( 68 ). Factor H in part controls complement activation on cells by binding to sialic acid.…”
Section: Complement From Implantation Through Placental Developmentmentioning
confidence: 99%
“…It is estimated that RPL affects over 1% of the general population and only half of the cases can be explained after a medical investigation. Each miscarriage increases the risk of another miscarriage to 15% [ 2 , 3 ]. Recurrent pregnancy loss [ 2 ] was defined according to the WHO definition as three or more consecutive spontaneous miscarriages before the 20th week of gestation [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Each miscarriage increases the risk of another miscarriage to 15% [ 2 , 3 ]. Recurrent pregnancy loss [ 2 ] was defined according to the WHO definition as three or more consecutive spontaneous miscarriages before the 20th week of gestation [ 4 , 5 ]. ESHRE guidelines indicated immunological diagnostics in case of two idiopathic pregnancy losses [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several gene polymorphisms affect the risk of RPL, such as matrix metalloproteinase genes [36], the methylenetetrahydrofolate reductase (MTHFR) gene [37], complement factors D and H [38], and genome wide methylation analysis [39], reflecting the complicated mechanisms that underlie the development of RPL. Previous studies have investigated the association of high levels of homocysteine and low levels of folate with the risk of RPL [40,41].…”
Section: Discussionmentioning
confidence: 99%